Women and Allies in Action: College Students as 'Diversity Workers' in the Activism Classroom - Seethaler, Ina (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2022)
Research on feminist pedagogy has analyzed activism-based teaching practices in introductory courses and special topics courses in Women’s and Gender Studies (WGS). Few studies have focused on courses that entirely center on feminist activism and have students implement weeks-long activism projects. In this article, I investigate how we can transfer an activist consciousness to our students, some of whom might not consider themselves feminists, might not have thought of themselves as activists, have not participated in any form of activism, or might be taking a WGS course only for general education or diversity credit. Using data collected in my “Women and Allies in Action” class via surveys, interviews, and analysis of students’ reflective writing, I assess which challenges hold students back and what motivates them to create and implement complex, creative, and sustainable feminist activism projects.